Attacking hepatitis B virus cccDNA – The holy grail to hepatitis B cure - Lucifora, Julie; Protzer, Ulrike (Journal of hepatology, 2016)
HBV deposits a covalently closed circular DNA form, called cccDNA, in the nucleus of infected cells. As the central transcription template, the cccDNA minichromosome is a key intermediate in the HBV life cycle. Its location in the nucleus makes cccDNA a difficult target for antivirals and immune response, and therefore it is responsible for chronicity of HBV infection. While little is known about the mechanisms involved in cccDNA formation, current research is accumulating data on the mechanisms regulating transcription from cccDNA, and the first potential targeting approaches have been reported. This review will summarize our knowledge about cccDNA biology and the latest advances in cccDNA targeting strategies in order to finally achieve an HBV cure.